Haplosaurus computes protein haplotypes for use in precision drug design. Issue 1 (December 2018) - Spooner, William; McLaren, William; Slidel, Timothy; Finch, Donna; Butler, Robin; Campbell, Jamie; Eghobamien, Laura; Rider, David; Kiefer, Christine; Robinson, Matthew; Hardman, Colin; Cunningham, Fiona; et al.
Abstract Selecting the most appropriate protein sequences is critical for precision drug design. Here we describe Haplosaurus, a bioinformatic tool for computation of protein haplotypes. Haplosaurus computes protein haplotypes from pre-existing chromosomally-phased genomic variation data. Integration into the Ensembl resource provides rapid and detailed protein haplotypes retrieval. Using Haplosaurus, we build a database of unique protein haplotypes from the 1000 Genomes dataset reflecting real-world protein sequence variability and their prevalence. For one in seven genes, their most common protein haplotype differs from the reference sequence and a similar number differs on their most common haplotype between human populations. Three case studies show how knowledge of the range of commonly encountered protein forms predicted in populations leads to insights into therapeutic efficacy. Haplosaurus and its associated database is expected to find broad applications in many disciplines using protein sequences and particularly impactful for therapeutics design. Proteoforms arise as protein isoforms or as protein haplotypes, which are the result of genetic variation. Here, the authors develop Haplosaurus, a database that computes protein haplotypes genome-wide from existing genotype data and analyse protein haplotype variability in the 1000 Genomes dataset.